2014
DOI: 10.1016/j.jval.2014.03.141
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study On Patient Safety Culture For Pharmacists In Japan

Abstract: A23the theoretical framework to guide the focus group discussions. Each session was audio-recorded, transcribed, and participant responses were analyzed for qualitative content. Results: Two, 60 minute focus groups (Total N= 12) were conducted. Time constraints and privacy issues presented as major themes in the discussions. Regarding advantages/disadvantages, participants emphasized the importance of counseling for the discussion of potential drug interactions and side effects of their medications and felt th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These results suggested that pharmacists might be more highly concerned with PS in Japan. [14] According to our original article, by using Lag time, which is the difference between the date of an incidence and the date on which it is reported, we could establish that Lag time for physicians was longer than that for nurses at Kyoto University Hospital in Japan. Likewise, Lag time for physicians was longer than that for non-MDs at Brigham and Women's Hospital in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that pharmacists might be more highly concerned with PS in Japan. [14] According to our original article, by using Lag time, which is the difference between the date of an incidence and the date on which it is reported, we could establish that Lag time for physicians was longer than that for nurses at Kyoto University Hospital in Japan. Likewise, Lag time for physicians was longer than that for non-MDs at Brigham and Women's Hospital in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Our crosssectional survey was conducted between December 2010 and May 2011. As PS performance is more active at larger hospitals, [14] of the 669 responding hospitals, the data from 42 hospitals did not include the necessary variables for this study. Therefore, they were excluded.…”
Section: Subjects Of This Studymentioning
confidence: 99%